Developing a proactive coping theory-based conceptual framework for sarcopenia management in aging societies: a mixed-methods study from China - Dai, Ruiqi; Feng, Xinqun; Weng, Yixi; Mao, Lei (Frontiers in Public Health, 2025)
IntroductionThis study proposes a public health strategy to combat sarcopenia in rapidly aging societies, addressing systemic gaps in preventive healthcare through a proactive, design-driven framework.MethodsA mixed-methods approach was adopted, integrating participatory questionnaires (n = 1,683) and grounded theory–analyzed interviews (n = 48). Stage classification was validated through triangulation of self-reported activity limitations, clinimetric scoring, and biomechanical assessments. The Analytic Hierarchy Process was employed to decode dynamic weighting mechanisms among physiological determinants, psychological factors, and fixed environmental parameters.ResultsThe study constructed a self-evaluated four-stage progression model applicable to urban contexts. By bridging clinical diagnostics with daily life narratives, the framework enables earlier risk identification outside healthcare settings. A novel mapping algorithm was devised, correlating patient-reported disease staging with evidence-based intervention tiers. The resultant three-tier system operationalizes cognitive reframing and behavioral reconfiguration mechanisms, aligning patient self-assessment with targeted intervention design.DiscussionThis interdisciplinary model synergistically addresses three critical objectives: healthcare resource optimization, social participation longevity enhancement, and disability trajectory modulation. By positioning design as an ecological mediator, the framework supports the transition of healthcare systems from acute care paradigms to preventive ecosystem orchestration, ultimately fostering equitable health resilience within aging societies.